A LysR Transcriptional Regulator Manipulates Macrophage Autophagy Flux During Brucella Infection - Zhang, Lu; Yu, Siyuan; Ning, Xinnuan; Fang, Hui; Li, Jie; Zhi, Feijie; Li, Junmei; Zhou, Dong; Wang, Aihua; Jin, Yaping (Frontiers in Cellular and Infection Microbiology, 2022)
Brucella, the intracellular bacteria, have evolved subtle strategies to efficiently survive and replicate in macrophages. However, the virulence effector proteins involved are still unclear. LysR-type transcriptional regulators (lttrs) are the largest regulator family with diverse function in prokaryotes. However, very little is known about the role of LysR regulators in the Brucella spp. Here, a BSS2_II0858 gene, encoded as one of the LysR-type regulators, was studied. We successfully constructed a BSS2_II0858 deletion mutant, Δ0858, and complementation strain CΔ0858 in Brucella suis S2. The cell apoptosis induced by B. suis S2 and its derivatives were detected by flow cytometry. The autophagy was then assessed by immunoblot analysis using the IL3I/II and p62 makers. In addition, the autophagy flux was evaluated by double fluorescent labeling method for autophagy marker protein LC3. Our studies demonstrated that B. suis S2 and its derivatives inhibited the programmed cell death in early stage and promoted apoptosis in the later stage during infection in RAW264.7 cells. The BSS2_II0858 gene was found to play no role during apoptosis according to these results. Compared with the wild-type strain, Δ0858 mutant can stimulate the conversion of LC3-I to LC3-II and markedly inhibited the autophagy flux at early stage leading to obvious autophagosome accumulation. This study explored the function of BSS2_II0858 gene and may provide new insights for understanding the mechanisms involved in the survival of Brucella in macrophages.